Adoption of Online Zakat Payment in Indonesia an Empirical Investigation: an Extension of the Technology Acceptance Model - Caniago, Siti Aminah; Ghofur, Abdul; Wahab, Wahab; Purwanto, Purwanto; Rozi, Feni Fitriani Putri (UIN Sunan Kudus, 2025)
This study investigates the determinants of online Zakat payment adoption in Indonesia by extending the Technology Acceptance Model (TAM) through the integration of Trust. It examines the effects of Perceived Usefulness (PU), Perceived Ease of Use (PEoU), and Trust on Attitude, as well as the influence of Attitude on Behavioral Intention. A quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) was employed, based on survey responses from 350 participants. The empirical findings show that all hypothesized relationships are significant (p < 0.05). Trust (t = 7.060), PU (t = 4.802), and PEoU (t = 4.222) each have significant positive effects on Attitude, while Attitude strongly influences Behavioral Intention (t = 7.546). The extended model demonstrates moderate predictive relevance for Attitude (R² = 51.9%). Among the antecedents, Trust has the largest effect size (f² = 0.174), indicating its central role in shaping attitudes toward online Zakat payment. These results validate the extension of TAM with Trust in the context of Islamic fintech adoption in Indonesia. The findings highlight the importance of security and transparency, suggesting that Zakat Management Organizations (ZMOs) should strengthen data protection systems and provide transparent reporting to foster positive user attitudes and enhance adoption intentions.